1999
DOI: 10.1046/j.1464-410x.1999.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of the bladder‐vascular selectivity of levcromakalim and YM934 in human tissues

Abstract: Only minor bladder-vascular selectivity for levcromakalim and YM934 could be detected in vitro. This suggests that neither drug would be tolerated clinically, although the results suggest that further development of bladder-selective KCO agents appears feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Our studies show that YM934 was more potent than (-)-cromakalim on both a dose (4.1-fold) and plasma concentration (2.9-fold) basis. These data are in agreement with previous reports suggesting a 2.7-fold potency di¡erence in rat portal vein [Uchida et al, 1994] and a 2-fold di¡erence in human detrusor strips [Martin et al, 1997;Chess-Williams et al, 1999]. Foster et al [1989] previously reported that cromakalim at 0.3 mg/kg, i.v.…”
Section: Discussionsupporting
confidence: 93%
“…Our studies show that YM934 was more potent than (-)-cromakalim on both a dose (4.1-fold) and plasma concentration (2.9-fold) basis. These data are in agreement with previous reports suggesting a 2.7-fold potency di¡erence in rat portal vein [Uchida et al, 1994] and a 2-fold di¡erence in human detrusor strips [Martin et al, 1997;Chess-Williams et al, 1999]. Foster et al [1989] previously reported that cromakalim at 0.3 mg/kg, i.v.…”
Section: Discussionsupporting
confidence: 93%
“…Agents are therefore needed that offer a greater selectivity for the bladder over the vasculature. YM-934 has been found to exert bladder:vascular selectivity in human tissues in vitro [59] but this is minor and of no clinical significance. ZD-6169 reduces the frequency of micturition in rats without any cardiovascular side effects [53] and inhibits bladder hyperactivity in rats at doses that produce minimal changes in blood pressure and heart rate [54], but only clinical trials will establish whether this selectivity is of therapeutic value.…”
Section: Potassium Channelsmentioning
confidence: 99%
“…The 12)] which is a potent vasodilator, that is 3-times more potent than LCRK, with particularly pronounced effect on coronary artery [92]. YM-934 (52) has been extensively evaluated in an attempt to delineate its pharmacological profile on cardiovascular [93][94][95], respiratory [96,97], and urinary [98,99] systems. A recent article by Astellas Pharmaceutical confirmed that a non-hypotensive dose of YM-934 significantly decreased coronary peripheral vascular resistances, increased coronary flow and enhanced myocardial recovery from transient coronary flow interruption in a dog model of impaired coronary circulation similar to unstable angina [100].…”
Section: Benzoxazinesmentioning
confidence: 99%